Reducing Maternal Mortality and Improving Maternal Health: Bangladesh and MDG 5 - Koblinsky, Marge; Anwar, Iqbal; Mridha, Malay Kanti; Chowdhury, Mahbub Elahi; Botlero, Roslin (Journal of Health, Population and Nutrition, 2009)
Bangladesh is on its way to achieving the MDG 5 target of reducing the maternal mortality ratio by three-quarters between 1990 and 2015, but the annual rate of decline needs to triple. Although the use of skilled birth attendants has improved over the past 15 years, it remains less than 20% as of 2007 and is especially low among poor, uneducated rural women. Increasing the numbers of skilled birth attendants, deploying them in teams in facilities, and improving access to them through messages on antenatal care to women, have the potential to increase such use. The use of caesarean sections is increasing although not among poor, uneducated rural women. Strengthening appropriate quality emergency obstetric care in rural areas reÂmains the major challenge. Strengthening other supportive services, including family planning and delayed first birth, menstrual regulation, and education of women, are also important for achieving MDG 5. Key words: Maternal health; Maternal mortality; Obstetric care; Quality of care; Bangladesh doi:10.3329/jhpn.v26i3.1896 J Health Popul Nutr 2008 Sept:26(3):280-294